2023
DOI: 10.1038/s41431-023-01326-8
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide meta-analysis identifies novel loci conferring risk of acne vulgaris

Abstract: Acne vulgaris is a common chronic skin disorder presenting with comedones, cystic structures forming within the distal hair follicle, and in most cases additionally with inflammatory skin lesions on the face and upper torso. We performed a genome-wide association study and meta-analysis of data from 34,422 individuals with acne and 364,991 controls from three independent European-ancestry cohorts. We replicated 19 previously implicated genome-wide significant risk loci and identified four novel loci [11q12.2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…FADS2 is a gene associated with lipid metabolism, upregulation of its expression can induce pro-inflammatory sebaceous gland activity (Zouboulis and Angres, 2021). Recent genome-wide association studies and meta-analysis have shown that FADS2 is a risk gene for acne vulgaris (Teder-Laving et al, 2023). TIMP-3 is a secreted protein that has a broad inhibitory effect on matrix metalloproteinases (MMPs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FADS2 is a gene associated with lipid metabolism, upregulation of its expression can induce pro-inflammatory sebaceous gland activity (Zouboulis and Angres, 2021). Recent genome-wide association studies and meta-analysis have shown that FADS2 is a risk gene for acne vulgaris (Teder-Laving et al, 2023). TIMP-3 is a secreted protein that has a broad inhibitory effect on matrix metalloproteinases (MMPs).…”
Section: Discussionmentioning
confidence: 99%
“…Acne vulgaris data are derived from GWAS studies and metaanalyses in European cohorts of EstBB, FinnGen and Lifelines, including 34,422 acne patients and 364,991 normal controls (Teder-Laving et al, 2023).…”
Section: Data Sourcesmentioning
confidence: 99%
“…The serum metabolite data were derived from a GWAS of 486 metabolites in blood from 7824 adults from two European populations, published by SoYoun Shin et al The 309 known metabolites were selected from this dataset 19 . The data on acne vulgaris were derived from a GWAS data of 34,422 patients with acne and 364,991 controls from three independent cohorts of European ancestry, published by Maris Teder-Laving et al in 2023 20 .…”
Section: Methodsmentioning
confidence: 99%
“… 19 For acne vulgaris, insights were integrated from the study by Teder‐Laving et al., which included 34 422 cases and 364 991 controls, identifying novel risk loci. 20 Genetic summaries for atopic dermatitis, psoriasis vulgaris, and urticaria were also sourced from the IEU Open GWAS database, with populations of 6224, 5072, and 1057 cases, respectively, and corresponding controls numbering 475 075, 478 102, and 482 892. 19 GWAS data for rosacea, involving 1195 cases and 211 139 controls, were procured from the FinnGen research consortium ( https://gwas.mrcieu.ac.uk/datasets/finn‐b‐L12_ROSACEA/ ).…”
Section: Methodsmentioning
confidence: 99%